Sarawak - Senegačnik, Jurij (Geografski obzornik, 2000)
Some of Sarawak's basic geographical features are presented, such as the geographical position, land-forms, climate, vegetation, population and economy. A special emphasis is laid on the tropical rainforest and the ethnic diversity of Sarawak.
Keywords: družbena geografija; fizična geografija; Malezija; regionalna geografija; Sarawak